PENGUJIAN MODUL PENGOLAH DATA TELEMETRI LAPAN-A3/IPB UNTUK MENGHASILKAN PRODUK LEVEL-0 (THE TESTOF LAPAN-A3/IPB TELEMETRY DATA PROCESSOR MODULE TO PRODUCE LEVEL-0 PRODUCT) - . Suhermanto (Jurnal Teknologi Dirgantara, 2016)
Telemetry data processing modulis a software for converting the LAPAN-A3/IPB telemetry data into raw sensor data (level-0 product). Telemetry data output from the High Data Rate Modulator-demodulator (HDRM) becomes an input for telemetry data processor, which has entered its setup parameter. The objective of the research is to test LAPAN-A3/IPB telemetry data processor implementation. The development and processing of telemetry data have been performed on a desktop computer that are divided into two stages, data decoding and data decomposition.The performance of the software has been tested using eight samples of raw-data, consisted of multi-spectral and camera matrix data obtained before and after the launch of the satellite. The test results showed, there were no missing telemetry data frames and damaged codeword in the process of decoding.Data on missing multi-spectral lines  and data on camera matrix frame lost in the process of decomposition were not found. It was concluded that the overall performance of the test result was that the system used was not able todecode, decompose, display quick-look LISA, or extractcamera matrix data in real-time.To perform as required, the computer performance needed to be increased up to 8 times. From this process, approximately 92% of CPU time were used for decoding and only about 8% were for the decomposition, extraction of data LISA, or extraction of data camera matrix.Improvement attempt by changing the word-size of 32bit processors into 64bit, did not give significant results and was only able to improve the processing speed of 8.1%. Abstrak:Modul pengolah data telemetri adalah softwareuntuk mengubah data telemetri LAPAN-A3/IPB menjadi data sensor yang masih mentah (produk level-0). Data telemetri keluaran dari perangkatHigh Data Rate Modulator-Demodulator (HDRM)menjadi masukan bagi pengolah data telemetri, yang parameter set-upnyatelah dimasukkan. Tujuan penelitian ini adalah untuk menguji implementasi pengolahan data telemetri satelit LAPAN-A3/IPB. Pembangunan dan pengolahan data telemetri telah dilakukan di komputer desktop yang dibagi dalam dua tahap, yaitu pendekodean data dan dekomposisi data. Unjuk kerja software telah diuji menggunakan delapan sampel raw-data, terdiri atas data multi-spektral dan matrik kamera yang diperoleh sebelum dan sesudah peluncuran satelit. Hasil uji memperlihatkan, tidak ditemukan frame data telemetri yang hilang dan codeword yang rusakpada proses pendekodean data. Juga tidak ditemukan data pada larikmulti-spektralyang hilang maupun data pada matrik kamera yang hilang pada proses dekomposisi. Dari uji kinerja secara keseluruhan didapat hasil bahwa sistem yang digunakan tidak mampu melakukan dekoda, dekomposisi, menampilkan quick-lookLISA,atau ekstraksi data matrik kamera secara real-time.Perlupeningkatan kinerja komputer hingga 8 kali lebih baik.Dari proses tersebut, sekitar 92% CPU time dipakai untuk pendekodean data dan hanya sekitar 8% untuk dekomposisi, ekstraksi data LISA,atau ektraksi data matrik kamera. Upaya perbaikan yang dilakukan dengan mengubah word-size prosesor dari 32bit menjadi 64bit hasilnya tidak signifikan dan hanya mampu memperbaiki kecepatan proses 8,1%.